2016
DOI: 10.1177/1533034615604454
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Electroporation in Bone and in the Surrounding Clinically Relevant Structures

Abstract: Skeletal metastases are a common cause of severe morbidity, reduction in quality of life and often early mortality. Consequently, improvements in therapies are necessary. Electroporation uses electric energy to alter cancer cell membrane permeability and enhance the local uptake of chemotherapeutics, thus leading to local tumor control. The aim of this study was to investigate the feasibility and safety of delivering electric field protocols causing electroporation of healthy bone and structures of clinical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…At higher magnification, it is possible to see the presence of newly formed bone in the whole trabecular bone around the electrodes, thus highlighting that the insertion procedure does not influence bone tissue viability. In fact, preexisting trabeculae among the electrodes were covered by osteoblasts (OBs) with evident evenly spread osteocytes [11]. A hydroxyapatite-coated titanium implant ( Figure 3) was implanted in a rabbit femoral condyle.…”
Section: Histological Findings Of Bone-implanted Medical Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…At higher magnification, it is possible to see the presence of newly formed bone in the whole trabecular bone around the electrodes, thus highlighting that the insertion procedure does not influence bone tissue viability. In fact, preexisting trabeculae among the electrodes were covered by osteoblasts (OBs) with evident evenly spread osteocytes [11]. A hydroxyapatite-coated titanium implant ( Figure 3) was implanted in a rabbit femoral condyle.…”
Section: Histological Findings Of Bone-implanted Medical Devicesmentioning
confidence: 99%
“…In the images, the double labeling of bone trabeculae is well evidenced. e length of fluorescent lines and the distance between each other are measurable parameters which can be used to evaluate bone turnover [11,15].…”
Section: Histomorphometric Findings Of Bone-implanted Medicalmentioning
confidence: 99%
“…Preclinical studies have demonstrated that in contrast to other ablative techniques, irreversible electroporation does not affect bone structure in the long term. 16 , 17 , 19 It only affects the cell membrane, while the tissue scaffold remains intact, thus preserving the mechanical competence of treated bone. Furthermore, irreversible electroporation does not affect or prevent osteogenic activity.…”
Section: Discussionmentioning
confidence: 99%
“…There are extensive studies on electroporation thresholds for specific tissues, such as liver, muscle, and brain, and on tumors present in these tissues, 25 , 26 , 32 , 43 , 44 but only a few preclinical studies on the effect of electroporation on bone and nerve tissue. 17 , 19 , 27 , 45 , 46 Thresholds for bone, bone tumors, and spinal cord have not yet been determined. Reported results on thresholds for electroporation of tumor tissue vary, depending on tumor histology and pulse parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation